Fighting Wrongs with Wrongs? How Canadian Anti-Trafficking Crusades Have Failed Sex Workers, Migrants, and Indigenous Communities - Maynard, Robyn (Atlantis)

(untitled) (Mount Saint Vincent University, 2015)
Indigenous populations, sex workers, and migrants have been legally, socially, and economically disenfranchised by the Canadian state in a multitude of ways—often in the name of “anti-trafficking.” In effect, state-led anti-trafficking enforcement measures fail to address the root causes of the harms created by past and present colonization, anti-sex work laws, and racist immigration measures and programs. This paper argues that anti-trafficking legislation and policies have been immeasurably harmful towards those they claim to protect.